2003
DOI: 10.1177/089686080302300207
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Anti-Chlamydia Pneumoniae Antibodies as Risk Factors of Cardiovascular Death in Incident Patients on Peritoneal Dialysis

Abstract: Objective Recently it has been pointed out that inflammation and infections caused by germs such as Chlamydia pneumoniae are independent cardiovascular risk factors for the general population, but information about these relationships in dialysis patients is scarce. This work was done to analyze the association of C-reactive protein (CRP) and IgG anti- Chlamydia pneumoniae antibodies (anti-Chlp-IgG) as independent cardiovascular risk factors in incident patients on continuous ambulatory peritoneal dialysis (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…The low level of plasma vitamin C as well as inflammatory status has been recently reported to be closely related to the increased risk of cardiovascular morbidity and mortality in either MHD or peritoneal dialysis (PD) patients [ 6 , 11 ]. Our previous cross-sectional analysis showed that low level of plasma vitamin C is negatively associated with the CRP level [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The low level of plasma vitamin C as well as inflammatory status has been recently reported to be closely related to the increased risk of cardiovascular morbidity and mortality in either MHD or peritoneal dialysis (PD) patients [ 6 , 11 ]. Our previous cross-sectional analysis showed that low level of plasma vitamin C is negatively associated with the CRP level [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, antioxidant levels, such as plasma vitamin C level and reduced glutathione level, were usually decreased [ 3 , 5 , 17 , 18 ]. It was documented that inflammation was associated with increased risk of cardiovascular morbidity and mortality in patients on dialysis [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other independent studies it was found that more than 80% had C-reactive protein serum levels in the range of positive inflammation, 35% had extracellular fluid volume expansion, and more than 60% were hypertensive (17,18).…”
Section: Clinical Outcomesmentioning
confidence: 87%